2005
DOI: 10.1051/0004-6361:20053337
|View full text |Cite
|
Sign up to set email alerts
|

Mapping extreme-scale alignments of quasar polarization vectors

Abstract: Based on a new sample of 355 quasars with significant optical polarization and using complementary statistical methods, we confirm that quasar polarization vectors are not randomly oriented over the sky with a probability often in excess of 99.9%. The polarization vectors appear coherently oriented or aligned over huge (∼1 Gpc) regions of the sky located at both low (z ∼ 0.5) and high (z ∼ 1.5) redshifts and characterized by different preferred directions of the quasar polarization. In fact, there seems to exi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
269
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(289 citation statements)
references
References 51 publications
20
269
0
Order By: Relevance
“…We first modeled the distribution of the debiased polarization degree in the full quasar sample (from Hutsemékers et al 2005, including objects with p < 0.6%). We found that it was reasonably well reproduced by a half-gaussian distribution of zero mean and unitary variance.…”
Section: Appendix A: the Determination Of δ P Linmentioning
confidence: 99%
See 1 more Smart Citation
“…We first modeled the distribution of the debiased polarization degree in the full quasar sample (from Hutsemékers et al 2005, including objects with p < 0.6%). We found that it was reasonably well reproduced by a half-gaussian distribution of zero mean and unitary variance.…”
Section: Appendix A: the Determination Of δ P Linmentioning
confidence: 99%
“…To interpret the large-scale alignments of quasar optical polarization vectors observed at redshifts z ∼ 1 (Hutsemékers 1998;Hutsemékers & Lamy 2001;Hutsemékers et al 2005) polarization induced by photon-pseudoscalar mixing along the line of sight has been invoked (Hutsemékers 1998;Jain et al 2002). Photon-pseudoscalar mixing generates dichroism and birefringence, the latter transforming linear polarization into circular polarization and vice-versa along the line of sight.…”
Section: Introductionmentioning
confidence: 99%
“…They found out that the low redshift regime (z < 0.06) of the data in the Union 2 catalogue (Amanullah et al 2010) is barely consistent with ΛCDM at 2−3σ because of a bulk flow towards the Shapley supercluster. Antoniou & Perivolaropoulos (2010) also applied the hemisphere comparison method to the SN Ia data of Union 2 and found a maximum anisotropy, which itself is statistically A&A 553, A56 (2013) not significant, but coincides with the bulk velocity flow axis (Feldman et al 2010;Kashlinsky et al 2009;Lavaux et al 2010), cosmic microwave background (CMB) low multipole moments (Bennett et al 2011;Copi et al 2010) and the quasar optical polarisation alignment axis (Hutsemekers et al 2008). Similar directions can be obtained by considering a dynamical dark energy fluid with an anisotropic equation of state in the wCDM model or in Chevallier-Polarski-Linder parametrisation (Cai & Tuo 2012).…”
Section: Introductionmentioning
confidence: 97%
“…§ e-mail: lixin1981@cqu.edu.cn. Akrami et al 2014;Quartin & Notari 2015), the spatial variation of the electromagnetic fine-structure constant (Webb et al 2011;King et al 2012;Molaro et al 2013), the largescale alignment of the quasar polarization vectors (Hutsemekers & Lamy 2001;Hutsemekers et al 2005), the large-scale bulk flow beyond the prediction of ΛCDM model (Kashlinsky et al 2009(Kashlinsky et al , 2010Watkins, Feldman & Hudson 2009), and so on. All of these phenomena arouse us to rethink the validity of the cosmological principle.…”
Section: Introductionmentioning
confidence: 99%